Intensity Of Rice Pest Pest Attack Using Keliling Observation Methods Linely Relationship with Outside Attacks of Arial Photograpy - Rahadi, I Ketut Satria; Wijaya, I Made Anom S; Tika, I Wayan (Jurnal BETA (Biosistem dan Teknik Pertanian), 2019)
Rat pests are pests that can cause crop failure in rice plant. The method used to calculate the number of rodent pest attacks is the method of sampling and obtaining aerial photographs. But from these two methods the level of attack produced is not known to correlate. So this study purpose to obtain a relationship between intensity of attack with area of attack rat pest of rice plants. The stages of this study were location surveys that were attacked by rat pests, preparation of tools, aerial photography, and sampling for the calculation of attack intensity, image processing, area attack, regression analysis and validation. The intensity of attacks is calculated using total calculations, while broad attacks are calculated using the aerial image processing method developed by Widodo. Regression analysis shows the relationship between the intensity of attack with the area of attack has a determination coefficient of 0.889 and the regression coefficient obtained y = 1.138x with an error factor of 8.947%. The intensity of rat pest attacks using linear related sampling methods with broad attack results from aerial photo analysis developed by Widodo